PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH DI SEKOLAH DASAR UNTUK MENINGKATKAN KETERAMPILAN ABAD KE-21 - Firliana Navani Shalsabilla; Gita Aprilia; Ladyta Agustin, Herliana; Iskandar, Sofyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the effect of problem-based learning  model in improving 21st-century skills in elementary school students. The PBL model places students in real-life problem situations that are relevant to everyday life, thus encouraging the development of critical thinking skills, problem solving, collaboration, communication, and independent learning. The learning process includes problem orientation, formation of study groups, independent or group investigations, and presentation and reflection of results. The application of this model has been proven to significantly increase students' motivation and active involvement in learning and 21st-century skills. With a student-centered learning approach and authentic problems, this model effectively facilitates the development of high-level thinking skills and essential social skills in the modern era. The implications of the study recommend the use of the problem-based learning model as the main strategy in elementary school learning to prepare students to face the challenges of the 21st century.